2019
DOI: 10.1016/j.jecp.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors underlying children’s acquisition and retrieval of sound–symbol association skills

Abstract: Letter knowledge is considered an important cognitive foundation for learning to read. The underlying mechanisms of the association between letter knowledge and reading skills are, however, not fully understood. Acquiring letter knowledge depends on the ability to learn and retrieve sound-symbol pairings. In the current study, this process was explored by setting preschool children's (N = 242, mean age = 5.57 years) performance in the acquisition and retrieval of a paired associate learning (PAL) task in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 31 publications
(59 reference statements)
5
31
2
Order By: Relevance
“…Differences between groups for the digit span task are not surprising, as this measure is often included in IQ test batteries, and academic achievement is known to correlate strongly with IQ (e.g., Wechsler, 1958 ; Kaufman and Lichtenberger, 2006 ; Deary et al, 2007 ; Hogan et al, 2010 ). Likewise, the differences observed for LLAMA-B fit well with previous research showing that explicit memory for cross-modal associations correlates with reading achievement 6 and other factors related to educational success ( Vellutino et al, 1975 ; Poulsen and Elbro, 2018 ; Ehm et al, 2019 ). Thus, the differences between high and low academic attainment participants are not necessarily attributable to education as such, but could be due to other factors that are known to correlate with academic attainment 7 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Differences between groups for the digit span task are not surprising, as this measure is often included in IQ test batteries, and academic achievement is known to correlate strongly with IQ (e.g., Wechsler, 1958 ; Kaufman and Lichtenberger, 2006 ; Deary et al, 2007 ; Hogan et al, 2010 ). Likewise, the differences observed for LLAMA-B fit well with previous research showing that explicit memory for cross-modal associations correlates with reading achievement 6 and other factors related to educational success ( Vellutino et al, 1975 ; Poulsen and Elbro, 2018 ; Ehm et al, 2019 ). Thus, the differences between high and low academic attainment participants are not necessarily attributable to education as such, but could be due to other factors that are known to correlate with academic attainment 7 .…”
Section: Discussionsupporting
confidence: 88%
“…Regression lines for each group are provided for illustration purposes. factors related to educational success (Vellutino et al, 1975;Poulsen and Elbro, 2018;Ehm et al, 2019). Thus, the differences between high and low academic attainment participants are not necessarily attributable to education as such, but could be due to other factors that are known to correlate with academic attainment 7 .…”
Section: Academic Attainment and Readingmentioning
confidence: 99%
“…Previous studies have reported EF skills to be essential in PAL (Ehm et al, 2019) and in early word reading (e.g., Becker et al, 2014; Cameron et al, 2012; Chung & McBride‐Chang, 2011). For example, Ehm et al (2019) showed that WM but not inhibition control was a unique predictor of PAL, which further predicted letter knowledge in German preschoolers. During the process of PAL, children have to stay focused on the stimuli presented, hold and maintain their visual or verbal representations in mind while simultaneously working with them to establish and secure their associations.…”
Section: Paired Associate Learning and Reading Developmentmentioning
confidence: 96%
“…Studies have reported significant associations between PAL, particularly visual–verbal, and word reading in typically developing children in alphabetic orthographies (e.g., Denish: Poulsen & Elbro, 2018; English: Hulme, Goetz, Gooch, Adams, & Snowling, 2007; Litt, de Jong, van Bergen, & Nation, 2013; German: Ehm et al, 2019) and also in Chinese (Chow, 2014, 2018a, 2018b; Georgiou, Liu, & Xu, 2017). However, our understanding of PAL and how it interacts with other cognitive and language skills contributing to word reading remain limited.…”
Section: Paired Associate Learning and Reading Developmentmentioning
confidence: 99%
See 1 more Smart Citation